Revision of Begonia (Begoniaceae) from the Melinau Limestone in Gunung Mulu National Park and Gunung Buda National Park, Sarawak, Borneo, including thirteen new species - Sang, Julia; Kiew, Ruth; Geri, Connie (Phytotaxa, 2013)
Besides Begonia conipila, 13 new species (Begonia apiensis, B. benaratensis, B. conniegeriae, B. divergens, B. lucychongiana, B. magentifolia, B. melinauensis, B. ramosissima, B. rhodoneura, B. umbratica, B. vulgare, B. yiii and B. xiphophylloides) and a putative natural hybrid between B. conipila and B. lucychongiana are described from the Melinau limestone. All these species are endemic in the Melinau limestone and 10 species are restricted to limestone habitats. The Melinau limestone includes the highest limestone hills in Malaysia with Gunung Api (1710 m) and Gunung Benarat (1615 m), which above 800 m are covered by montane forest. The vegetation types and habitats of each species are described. Conservation-wise, all are of Least Concern following IUCN criteria and categories, except for B. apiensis that is extremely local and threatened by tourist activities and is designated Rare following Malaysian criteria and categories.